Recursive identification of an arterial baroreflex model for the evaluation of cardiovascular autonomic modulation. (1st November 2015) - Le Rolle, Virginie; Beuchee, Alain; Praud, Jean-Paul; Samson, Nathalie; Pladys, Patrick; Hernández, Alfredo I.
Abstract: The evaluation of the time-varying vagal and sympathetic contributions to heart rate remains a challenging task because the observability of the baroreflex is generally limited and the time-varying properties are difficult to take into account, especially in non-stationnary conditions. The objective is to propose a model-based approach to estimate the autonomic modulation during a pharmacological challenge. A recursive parameter identification method is proposed and applied to a mathematical model of the baroreflex, in order to estimate the time-varying vagal and sympathetic contributions to heart rate modulation during autonomic maneuvers. The model-based method was evaluated with data from five newborn lambs, which were acquired during injection of vasodilator and vasoconstrictor drugs, on normal conditions and under beta-blockers, so as to quantify the effect of the pharmacological sympathetic blockade on the estimated parameters. After parameter identification, results show a close match between experimental and simulated signals for the five lambs, as the mean relative root mean squared error is equal to 0.0026 (±0.003). The error, between simulated and experimental signals, is significantly reduced compared to a batch identification of parameters. The model-based estimation of vagal and sympathetic contributions were consistent with physiological knowledge and, as expected, it was possible to observe an alteration of the sympathetic response under beta-blockers. The simulated vagal modulation illustrates a response similar to traditional heart rate variability markers during the pharmacological maneuver. The model-based method, proposed in the paper, highlights the advantages of using a recursive identification method for the estimation of vagal and sympathetic modulation. Abstract : Highlights: Recursive identication algorithm coupled to a model of the baroreflex. Time-varying estimation of autonomic activity during pharmacological manoeuver. Estimation of individualized sympathetic and parasympathetic modulation in a pediatric context. Validation of the model-based method using traditional time-frequency analysis.